Pengaruh Teamwork dan Self-Efficacy Terhadap Produktivitas Karyawan Pada PT United Farmatic Indonesia: The Influence of Teamwork and Self-Efficacy on Employee Productivity at PT United Farmatic Indonesia - Zihan Natasya; Usran Masahere (CV Warnak Johanna Nusantara, 2026)
Employee productivity is an important factor in supporting the achievement of organizational goals. Optimal productivity levels can be influenced by various factors, including teamwork and self-efficacy. Effective teamwork enables good communication and coordination among employees, while self-efficacy refers to an individual’s belief in their ability to accomplish work tasks. This study aims to examine the effect of teamwork and self-efficacy on employee productivity at PT. UFI. The research employed a quantitative method by distributing questionnaires through Google Forms. The population of this study consisted of 105 office employees at PT. UFI, with 77 respondents selected using a purposive sampling technique. Hypothesis testing was conducted using t-tests and an F-test. The results indicate that teamwork has a positive and significant effect on productivity (t-value = 4.128 > 1.992; sig. = 0.003), and self-efficacy also has a positive and significant effect on productivity (t-value = 4.913 > 1.992; sig. = 0.000). Simultaneously, teamwork and self-efficacy significantly affect productivity, as indicated by an F-value of 137.842 > 3.11 with a significance value of 0.000. In conclusion, teamwork and self-efficacy contribute 78.3% to employee productivity, while the remaining 21.7% is influenced by other variables not examined in this study.